2011
DOI: 10.1007/s13361-011-0122-z
|View full text |Cite
|
Sign up to set email alerts
|

MALDI Mass Spectrometric Imaging of Lipids in Rat Brain Injury Models

Abstract: Matrix-assisted laser desorption ionization/imaging mass spectrometry (MALDI IMS) with a time-of-flight analyzer was used to characterize the distribution of lipid molecular species in the brain of rats in two injury models. Ischemia/reperfusion injury of the rat brain after bilateral occlusion of the carotid artery altered appearance of the phospholipids present in the hippocampal region, specifically the CA1 region. These brain regions also had a large increase in the ion abundance at m/z 548.5 and collision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(126 citation statements)
references
References 32 publications
9
117
0
Order By: Relevance
“…Previous works demonstrated that the tissue damage produced during ischemia is accompanied by a deregulation of the Na + /K + -ATPase (or Na + pump) inducing changes in the relative abundance of Na + /K + adducts [27]. In the case of cancer, it is well known that tumor cells are usually in environments with lower pH than healthy tissue, probably owing to their unbalanced metabolism [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Previous works demonstrated that the tissue damage produced during ischemia is accompanied by a deregulation of the Na + /K + -ATPase (or Na + pump) inducing changes in the relative abundance of Na + /K + adducts [27]. In the case of cancer, it is well known that tumor cells are usually in environments with lower pH than healthy tissue, probably owing to their unbalanced metabolism [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…As with the brain PL analyses, we examined total PL levels which showed that while PC, PE, SM, and PI levels were lower in injured mice relative to controls at this 3 mo postinjury time point, only a decrease in PI among injured mice was statistically significant (F (1,20) ϭ21, PϽ0.01; Fig. 8).…”
Section: Plasma Pl Levels Following CCI Tbi At 3 Mo Postexposurementioning
confidence: 99%
“…MALDI-IMS has been used extensively to study lipids in tissue because IMS can resolve their structures and compositional diversity [32,33]. For example, MALDI-IMS has been used to visualize the heterogeneous distribution of PC species in mouse brains [34], and effects of traumatic brain injury on the differential localization of PCs in rat brains [35]. Furthermore, MALDI-IMS detected alterations in phospholipid zonation in human livers with steatosis or nonalcoholic steatohepatitis (NASH) [36], and MALDI-TOF was used to measure serum lipidomic profiles in patients with NASH [37].…”
Section: Introductionmentioning
confidence: 99%